Análise molecular de polimorfismos dos genes da família GST em pacientes com carcinoma espinocelular de cabeça e pescoço tratados com quimioterapia e/ou radioterapia - Maniglia, Mauricio Pereira (2017)
Head and neck cancer are among the ten most common types of cancer in Brazil, accounting for a high mortality rate in the country. Polymorphisms in genes of xenobiotic metabolizing enzymes such as the glutathione-S-transferases (GSTs) family may lead to decreased ability to inactivate activated carcinogens (alcohol and cigarette substances) and increase the risk for cancer, in addition to influencing the response to treatment of chemotherapy and/or radiotherapy of this disease. Objective: To investigate the association between GSTM1 and GSTT1 null genotypes and the A313G and C341T polymorphisms of the GSTP1 gene and head and neck cancer; to verify the association between these polymorphisms and anatomical site of tumor occurrence and clinical-pathological characteristics of patients with this type of cancer treated with chemotherapy and/or radiotherapy; to evaluate the influence of polymorphisms in relapse-free and survival time of patients with head and neck cancer treated with chemotherapy and/or radiotherapy. Patients and Methods: In this retrospective case-control study, 711 subjects were included, 197 patients diagnosed with head and neck squamous cell carcinoma by Otorhinolaryngology and Head and Neck Surgery Service of Base Hospital, São José do Rio Preto (FAMERP/HB) and 514 individuals with no history of neoplasia from the Hemocenter (FAMERP/HB). The variables analyzed were: gender, age, smoking habit and alcohol consumption, anatomical site of tumor clinical-pathological features of the tumor and treatment with chemotherapy and/or radiotherapy. Genotyping of the polymorphisms was performed by Polymerase Chain Reaction (PCR) for GSTM1 and GSTT1 and PCR-Restriction Fragment Length Polymorphisms (PCR-RFLP) for A313G and C341T polymorphisms of the GSTP1 gene. In the GSTP1 gene genotype frequencies of the A313G and C341T polymorphisms were evaluated for Hardy-Weinberg Equilibrium (HWE), Chi-square test and haplotype analysis. Multiple Logistic Regression Test was performed to determine the effect of the variables analyzed on head and neck cancer. Results: Genotypic frequencies of GSTP1 A313G and C341T polymorphisms showed in HWE in both groups (case and control, p>0.05); the GSTP1 A313G/C341T haplotypes differed significantly between case and control groups (Case group: A313/C341, p=0.013; A313/T341, p=0.019; Control group: G313/C341, p=0.015). Advanced age (≥59, p<0.001), male gender (p=0.040), smoking habit (p <0.001), alcohol consumption (p<0.001), GSTT1 (p<0.001), GSTM1 (p<0.001), GSTP1 A313G (p=0.037) polymorphisms showed significance in the risk for head and neck cancer. The GSTP1 C341T polymorphism (p=0.688) did not show significance with the risk for this type of cancer. Polymorphisms were not associated with the anatomical site, clinical-pathological features of the tumor, relapse-free, and patient survival time (p>0.05). Conclusion: The presence of the null genotype GSTM1 is associated with increased risk for head and neck cancer, while the null genotype GSTT1 and GSTP1 A313G contributes to the reduction of risk in this tumor type. The GSTs polymorphisms investigated are not associated with clinical-pathological features of the tumor, relapse-free or survival time of patients treated with chemotherapy and/or radiotherapy. Further studies with amplification of the sample group may contribute to the clarification of the role of polymorphisms in GST family genes in individual differences of patients in response to chemotherapy and/or radiotherapy treatments and to identify biomarkers of susceptibility.